AI And Fan Fiction Creative Writing: Cross-disciplinary Perspectives - Di Pardo Léon-Henri, Dana (The Journal of Studies in Language, Culture, and Society, 2025)
This study explores the intersection of creativity, Artificial Intelligence (AI), and education, with a focus on a graduate-level fan fiction writing course designed for non-specialists. As technology reshapes our world, education must adapt, and this research investigates how AI tools—such as text generators, error correction systems, and text-to-image technologies—can influence the creative writing process. Drawing insights from 20 students across various fields, the study examines how AI aids productivity and opens new creative avenues, while also raising questions about originality, ethics, and authorship. Central to this research is the didactic approach, which advocates for AI as a tool that enhances creativity rather than replacing critical thinking or artistic expression. By incorporating AI into the classroom, the study explores how educators can guide students in navigating both the potential and limitations of technology, ensuring it supports creativity while fostering independent thinking, ethical decision-making, and authentic self-expression. Ultimately, this research demonstrates that with a reflective teaching and learning approach, AI can be a powerful tool for creative exploration without compromising the core values of education.